Reimagining Human Security in Nigeria: Leveraging Effective Public Administration for Sustainable Solutions - Leke Kayode Onabanjo; Lawal A. Bakare; Oluwafisayo O. Falowo (Universitas Airlangga, 2026)
Abstract Security challenges constitute a global phenomenon, yet their dynamics and management vary significantly across contexts. The Nigerian case raises important concerns regarding government effectiveness in addressing contemporary security challenges and reflects broader issues of governance capacity. Effective public administration plays a critical role in carrying out government functions, particularly in relation to state activities, institutionalization, public service delivery, and the protection of lives and property. This study investigates the causes of insecurity in Nigeria and examines how effective public administration can address these persistent challenges. Using an exploratory approach, the study conducts a thematic analysis of the underlying causes of insecurity and the role of effective public administration as a potential remedy. The findings indicate that governance failure and weak institutionalization are major root causes of Nigeria’s security challenges. They also show that the current structure of public administration in Nigeria remains inadequate for effective security oversight. When properly implemented, however, effective public administration can help address security challenges by strengthening the processes and structures that promote community welfare, justice, and social order. The study concludes that although effective public administration significantly influences security outcomes in Nigeria, stronger political will is required to enhance its impact. This study contributes to the literature on human security and public administration by identifying governance failure and institutional weakness as underlying factors shaping the security challenges confronting the Nigerian state. Keywords: public administration; security; management; governance; institutions